The diets of school‐aged Aboriginal youths in Canada: a systematic review of the literature. Issue 3 (22nd May 2014) - Gates, A.; Skinner, K.; Gates, M.
Abstract Background Most national surveys examining diet leave large segments of the Aboriginal population under‐represented. The present study aimed to: (i) review primary research studies that investigated the dietary intakes of Canadian school‐aged Aboriginal youths; (ii) summarise the tools and methodologies currently used to measure diet in this population; and (iii) identify knowledge gaps and suggest areas of future research. Methods A systematic review of research published between January 2004 and January 2014 related to the diets of Canadian school‐aged (6–18 years) Aboriginal youths was undertaken, including Medline, Scopus, ERIC, Web of Science and Google Scholar databases. Studies were summarised based on purpose, year, sample population, setting, dietary assessment method and main findings. Results Twenty‐four studies were reviewed, all of which were cross‐sectional in design. Most (n = 16; 67%) were from Ontario or Quebec, investigated the diets of First Nations (n = 21; 88%) youths and took place in remote or isolated settings (n = 18; 75%). Almost all of the studies used the 24‐h recall to assess intake (n = 19; 79%), of which 89% used a single recall. The findings suggest that the diets of Aboriginal youths could be improved. Of particular concern are inadequate intakes of vegetables and fruit, milk and alternatives, fibre, folate, vitamin A, vitamin C, calcium and vitamin D, concomitant with an excess consumption of sugar sweetened beverages, snacks and fast foods. Traditional foods remain important but tend to be consumed infrequently. Conclusions The diets of Canadian Aboriginal youths are energy‐dense and nutrient‐poor. The diets of Inuit and Métis youths, in particular, and perceptions of a balanced diet warrant further investigation.